Private management costs of Popillia japonica: a study of viticulture in Italy - Straubinger, Franziska B.; Venus, Terese E.; Benjamin, Emmanuel O.; Sauer, Johannes (Frontiers in Insect Science, 2023)
The Japanese beetle (Popillia japonica) is classified as a high-priority pest in the European Union and is reported to have caused extensive damage to grapevine leaves in Italy. As there are few studies, which measure the beetle’s socio-economic impact, we conduct a first descriptive assessment of grapevine farmers’ perception of the beetle’s impact and assess the pest’s effect on private management costs using a partial budgeting approach. Our sample includes data from 65 producers and 118 vineyard plots. In terms of farmers’ perception, we find that farmers anticipate increased management costs and believe a further spread of the beetle will lead to at least moderate yield and quality damages for the majority of plots (58-91%). While farmers do not expect to stop grapevine cultivation for the majority of vineyard plots, affected farmers they believe it is likely to very likely for 29% of plots. We also find that affected farmers rate their vines’ resilience higher than unaffected farmers do. Using a partial budgeting approach, we find that a Japanese beetle infestation leads on average to a net income decrease of around €2727 per hectare. This decrease is due to an average increase in labor costs of around €1715. Additionally, an average yield reduction that results in a revenue loss of around €966 and additional control costs of around €47 per infested hectare, further contribute to the net income decrease. Even though the small number of observations does not allow us to make conclusions about the beetle’s impact on the Italian viticulture sector as a whole, our findings provide first insights and demonstrate the need for environmentally friendly and effective control products that can replace labor-intensive manual control measures, which are currently applied in Japanese beetle infested vineyards.